Does Mode of Interaction Impact Emotional Labour? A Mixed Method Study Among Service Employees in India - Shagirbasha, Shameem (Asian Journal of Empirical Research, 2015)
The emergence of service sectors has signaled way to employment to greater extent across the various countries (Lee and Wolpin, 2006). Service sectors has catered way to many service jobs which require interpersonal contacts with customers and employees are often required to engage in emotional labour (EL). Emotions are integral part of employees and customer interactions and understanding of emotional labour will benefit the service sectors to manage employee-customer relationships better. The objective of this study is to find whether emotional labour in hotels and call centres differs based on mode of interaction. To begin with, 12 in-depth Interviews were conducted from service employees. Then, standardized questionnaires were distributed to the employees to collect data through Survey method. Statistical analysis was done on 452 responses from hotels and call centres. As hypothesized, mode of interaction has an impact on emotional labour. The study also discusses managerial and theoretical implications along with limitations and areas of future research.